The tip of the iceberg? Protest and crisis–prone development in Central and Eastern Europe since 1989 - Jaitner, Felix; Spöri, Tobias (Socio.hu Társadalomtudományi Szemle, 2017)
Since the outbreak of the financial and economic crisis in 2008, protests against austerity and raising social inequality have increasingly taken place in many regions of the world. Central and Eastern Europe is one of those regions, and has recently experienced several large–scale protest movements. These protests were partially triggered by intensified austerity measures, higher unemployment rates and growing dissatisfaction with democracy. However, the particular reasons to protest are diverse, ranging from environmental to social or anti–corruption issues. Despite the differences that exist in Central and Eastern Europe countries, we argue that they share a common pattern in terms of the societal environment of protest. As a first step, we will critically assess the forms of protest participation in Central and Eastern Europe and map out common features of the identified crisis–prone development since 1989. In the subsequent part, we will argue that such features as the growing gap between the political elite and citizens, harsh individual economic conditions and a high level of frustrated expectations have become more visible and have heavily contributed to the increasing unrest. We conclude that the crisis–prone development since 1989 has created an ambivalent ecology of protest in Central and Eastern Europe. The vast majority of citizens face economic hardship and do not have the means to interfere with or participate in democratic processes as effectively as the political and economic elites do. A growing number of citizens, however, appear to be more willing to raise their voices visibly in public. Secondly, the increase in protests indicates a deeper societal crisis. In this sense, Central and Eastern Europe can be understood as a “laboratory” for testing the social conditions of democracy. Keywords: Central and Eastern Europe, protest, crisis, transformation